A Review on Energy Consumption Model on Hierarchical Clustering Techniques for IoT- based Multilevel Heterogeneous WSNs Using Energy Aware Node Selection - Matthew Iyobhebhe; Abdooulie Momodou. S. Tekanyi; K. A. Abubilal; Aliyu. D Usman; H. A. Abdulkareem; Yau Isiaku; E. E Agbon; Elvis obi; Ishaya Chollom Botson; Chukwudi Ezugwu; Ridwan. O. Eleshin; Fatima Ashafa; Saba Abubakar; Abubakar Umar; Ajayi Ore-Ofe; Paul Thomas Muge (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
This review article scrutinizes the energy consumption model related to hierarchical clustering methods in IoT-based multi-tier heterogeneous networks (WSNs). Since energy efficiency is vital to prolong the operational activities of sensor nodes, this review article concentrated on energy-aware node selection as a significant technique for improving energy consumption. The review article deliberates on the challenges posed by dynamic wireless sensor network conditions, node heterogeneity like energy-based, and scalability challenges that affect energy management. This review article scrutinizes the energy consumption model related to hierarchical clustering methods in IoT-based multi-tier heterogeneous networks (WSNs). Since energy efficiency is vital to prolong the operational activities of sensor nodes, this review article concentrated on energy-aware node selection as a significant technique for improving energy consumption. We scrutinize different factors affecting efficient node selection, comprising residual energy, transmission distance, and sensor node reliability while juxtaposing these techniques with traditional node selection schemes. Furthermore, the importance of developed modeling techniques was highlighted. Finally, future research directions were outlined, by accentuating the incorporation of energy harvesting and collective models to improve the stability and operation of Wireless Sensor Networks. This holistic overview aims to offer appreciated insights for authors and practitioners in WSNs.